New sacrificial cladding system for the reduction of blast damage in reinforced concrete structures - Codina, Ramon Humberto (2017)
Over the past few decades, explosive devices have become the weapon of choice for many terrorist attacks. In some of these attacks, large amounts of explosives are detonated within a short distance of building structures. It has been shown that current design methods are inadequate for the prevention of progressive collapse. The protection of key elements, such as columns, is necessary to prevent this catastrophic response sufficiently. This article discusses the performance of a new sacrificial cladding that protects reinforced concrete members under blast loading. It consists of reinforced resin panels with an insulation layer. For comparison purposes, two reinforced concrete members were previously experimentally studied, a reinforced concrete column without protection and reinforced concrete column with classical steel jacketing. It can be observed from the experimental results that the new sacrificial cladding achieves an important reduction in damage and displacements.